2006
DOI: 10.2514/1.15403
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Blade Cooling Studies at Texas A&M University: 1980-2004

Abstract: Gas turbines are used extensively for aircraft propulsion, land-based power generation, and industrial applications. Developments in turbine cooling technology play a critical role in increasing the thermal efficiency and power output of advanced high-temperature gas turbine engines. Gas turbine blades are cooled internally by passing the coolant through several rib-enhanced serpentine passages to remove heat conducted from the outside surface. External cooling of turbine blades by film cooling is achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 161 publications
(135 reference statements)
0
42
0
1
Order By: Relevance
“…Compared to the impingement onto the flat plate, the impingement heat transfer of the pin-finned surface may increase or decrease depending on the spent air direction. Akella and Han [15,16] found that the pin-finned surface performed better than the dimpled surface at a lower jet Reynolds number. However, at higher jet Reynolds numbers, the dimpled surface performed better than the pin-finned surface.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared to the impingement onto the flat plate, the impingement heat transfer of the pin-finned surface may increase or decrease depending on the spent air direction. Akella and Han [15,16] found that the pin-finned surface performed better than the dimpled surface at a lower jet Reynolds number. However, at higher jet Reynolds numbers, the dimpled surface performed better than the pin-finned surface.…”
Section: Introductionmentioning
confidence: 98%
“… 16. showed the comparison of the local Nusselt number distributions on the inline and staggered pin-fin plates at the Reynolds number of 35,000 with the maximum crossflow scheme.…”
mentioning
confidence: 99%
“…유동간섭물 중 요철의 경우 다양한 형상과 배열이 가능하 며 이러한 여러 가지 요철 형상에 대한 냉각성능 평가 및 최 적화에 관련된 연구가 Han [1], Taslim et al [2], Kim and Kim [3], Lee and Kim [4] …”
Section: 서 론unclassified
“…Gas turbines are widely applied to electric power generation, aviation propulsion, gas transportation and ship manufacture [1]. With the purpose to enhance turbine efficiency and output, the inlet temperature of modern gas turbines grows higher and higher.…”
Section: Introductionmentioning
confidence: 99%